Processing method of brewing instant integral-flower tremella - XIAO GUOSHUI; XIAO SHANGBING; XIAO SHIRUI; XIAO GUOBIN; GUO WEIXING; XIAO SHANGWEN (2016)
The invention discloses a processing method of brewing instant integral-flower tremella. The brewing instant integral-flower tremella is prepared by the steps of cleaning, blanching, pre-freezing and performing microwave vacuum freeze-drying treatment on the whole fresh tremella. The tremella product prepared by the method provided by the invention can maintain the original integral flower shape and color of the tremella, has chrysanthemum or peony shapes and integral flower shape, has the fragrant smell of the tremella after being brewed, can maintain the original viscosity, mouthfeel, flavor and nutrients of the tremella to the greatest extent, and has the advantages of long shelf life, portability, capability of being brewed and eaten instantly and the like. The drying method provided by the invention has the characteristics of energy saving and high efficiency and can save energy by more than 60% as compared with the traditional freeze-drying method. 本发明公开了种冲泡速食整花银耳的加工方法，其是将整朵新鲜银耳经清洗、漂烫、预冻和微波真空冷冻干燥处理，制得所述